Spring wheat mixtures in northern crop production: ability of mixtures to buffer disease development and yield loss caused by Septoria nodorum - Karjalainen, Reijo (Agricultural and Food Science, 1986)
Epidemic development of Septoria nodorum was studied in pure stands and mixtures of two spring wheat cultivars Tähti (susceptible) and Kadett (moderately resistant) in 1983—1985. Apparent infection rates in the mixture were similar to that of the more resistant pure stand. In all three years, disease levels in mixed stands were lower than the arithmetic mean of the pure stands. The yield experiments indicated that under low or moderate disease stress mixtures can buffer yield reduction effectively. However, when disease levels were high, mixtures appeared to be less effective in that respect. The results are discussed in relation to possible mechanisms of intraspecific mixtures to retard non-specialized pathogens. The use of wheat mixtures to prevent disease induced yield losses caused by S. nodorum is also discussed.